Re-classification of agro-ecological regions of Zimbabwe in conformity with climate variability and change - Mugandani, Raymond; Wuta, M; Makarau, A; Chipindu, B (African Crop Science Journal, 2021)
Zimbabwe was divided into five agro-ecological regions in the 1960s, however, the increased variability of rainfall has possibly affected the agro-ecological region boundaries. This study re-classifies the agro-ecological regions (natural regions) of Zimbabwe using soil data, mean-annual rainfall and length of growing season. Rainfall data from selected meteorological stations covered the period 1972- 2006. Soil data were obtained from the soil map of Zimbabwe, while length of growing seasons data were obtained from the FAO New Local Climate database. The simple limitation approach was used to produce a suitability zone map using all the parameters with the same weighting. The results show that the number of regions remained the same although the size of the regions had changed. The findings from this study point to an increase in the size of Natural Regions (NRs) I, IV and V by 106, 5.6 and 22.5 %, respectively. Natural Regions II and III decreased by 49 and 13.9%, respectively. The shrinking of Natural Regions II and III which are the main food producing areas in Zimbabwe, point to possible reduction in food production and thus problems of food insecurity. The shifting of the NRs boundaries observed in this study strongly points to evidence of climate variability and change.